Penanaman Karakter Religius dan Karakter Disiplin Melalui Pembiasaan Sholat Dhuha Di Madrasah Ibtidaiyah - Danuwara, Prima; Giyoto, Giyoto (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to describe (1) the cultivation of religious character and discipline through the habit of Duha prayer at Mi Muhammadiyah Karangduren Sawit Boyolali, (2) the values ??contained in the religious character and discipline character that exist in the habit of Duha prayer. The research is qualitative research with field research to find out about cultivating religious character and disciplined character through the practice of dhuha prayers at Mi Muhammadiyah Karangduren. The subject of this research is the Mi Muhammadiyah Karangduren teacher. Data collection in this research used interviews, observation, and documentation. then, the data analysis used is data reduction, presenting the data, and drawing conclusions. The results of this research show that cultivating religious character and discipline can be implemented through the practice of Dhuha prayers as has been implemented at Mi Muhammadiyah Karangduren Sawit. The religious character that is instilled through congregational dhuha prayers contains several values, such as the value of honesty which is reflected when students come to the madrasah and have not performed ablution, meaning they must first perform ablution with self-awareness. Divine values ??are symbolized by the differences that exist, but the students remain side by side, straightening their rows and prostrating themselves together to Allah. As well as instilling istiqomah in students to participate in the dhuha prayer from start to finish dhikr and memorizing Asmaul Husna without disturbing their friends and the value of cooperation that exists when preparing a place for dhuha prayer even though the schedule is given in grades 4-6. Then the character of discipline is instilled, such as discipline regarding the time at which students arrive before the Duha prayer begins, namely 07.00, and discipline in carrying out tasks according to the assignment.